2018
DOI: 10.1029/2018gl079751
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of Englacial Firn Aquifer Thickness From Ice‐Penetrating Radar Sounding in Southeastern Greenland

Abstract: An extensive perennial firn aquifer was previously mapped in Helheim Glacier, Southeast Greenland. However, critical constraints on aquifer thickness have been so far unobtainable without expensive field observations. Here we present a novel method that combines very high frequency airborne deep ice radar and ice sheet modeling to retrieve aquifer thickness and its evolution at Helheim Glacier. Using 2012–2014 radar measurements, we identify three aquifers of 4–25 m thick, with a total area of 1,934 km2 and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 55 publications
(66 reference statements)
1
19
0
Order By: Relevance
“…The firn aquifer responds dynamically to surface forcing. This supports findings of Chu et al (2018), who identified annual changes in aquifer thickness that corresponded to changes in surface mass balance.…”
Section: Discussionsupporting
confidence: 91%
“…The firn aquifer responds dynamically to surface forcing. This supports findings of Chu et al (2018), who identified annual changes in aquifer thickness that corresponded to changes in surface mass balance.…”
Section: Discussionsupporting
confidence: 91%
“…This approach can be used when correcting attenuation effects or constraining the bed conditions using layer power (MacGregor and others, 2015b; Chu and others, 2018b). Modeled attenuation can be compared to observations to constrain englacial temperature, parameterize basal conditions to match surface velocities or to quantify englacial water from persistent firn aquifers (Forster and others, 2014; Schroeder and others, 2016c; Chu and others, 2018a; Holschuh and others, 2019).…”
Section: Radio-wave Attenuationmentioning
confidence: 99%
“…In 2011, a firn aquifer in the upstream region of Helheim Glacier (southeast Greenland) was studied with ice coring and ground-penetrating radar (GPR) methods (Forster et al, 2014;Koenig et al, 2014). Airborne radar data have been used to measure the depth and extent of the aquifer (e.g., Chu et al, 2018;Miège et al, 2016), but the utility of radar sampling beneath the aquifer is limited because liquid water increases radar attenuation rates. Magnetic resonance sounding (MRS) methods have been used to estimate the volume of water stored within the aquifer; however, vertical resolution and the aquifer base were poorly resolved (e.g., Legchenko et al, 2018aLegchenko et al, , 2018b.…”
Section: 1029/2020gl089335mentioning
confidence: 99%